Grossschutzgebiete in den slowakischen Karpaten als Kompensation urbaner Verdichtung - Heino Meessen; Juraj Švajda; Thomas Kohler; Vladimíra Fabriciusová; Dobromil Galvánek; Miroslav Buraľ; Marcela Káčerová; Ján Kadlečík (Revue de Géographie Alpine)
In Eastern Europe’s westernmost mountain region, the Carpathians, the Slovak State Nature Conservancy is preserving a unique biodiversity in line with directives of the European Union. This is being done in large protected areas (LPAs). In this paper, we discuss current challenges of LPA management with a particular focus on contradictions between local people’s views and nationally to internationally determined sectoral planning strategies. We take stock of the benefits LPAs offer local populations, analyse the reasons for conflict between conservation interests from outside the region and local people’s vital needs, and explore ways of uncovering, tackling, and solving land use conflicts at the interface of national or international conservation interests and sustainable local development. Slovak and Swiss universities (Banská Bystrica, Žilina, and Bern) and nature conservation partners adapted, tested, and analysed a transdisciplinary research approach to mitigate land use conflicts in and around LPAs. . A joint Slovak–Swiss financing mechanism enabled Slovak project partners to implement small innovative projects proposed by local stakeholders – so-called Seed Money Actions (SMAs). First results show that this might be a fruitful new form of cooperation between protected area managers and local populations, as it may ultimately lead to a higher acceptance of nature conservation among locals while offering Slovak mountain farmers more tangible benefits from nearby protected areas.